Experimental study on the seismic damage behavior of aeolian sand concrete columns. Issue 2 (3rd March 2020) - Wang, Yaohong; Chu, Qi; Han, Qing; Zhang, Zeping; Ma, Xiaoyan
ABSTRACT: In order to promote the application of aeolian sand in concrete frame structures, it is necessary to study the seismic damage performance of aeolian sand concrete columns. In this paper, 4 concrete column specimens with different replacement percentages of aeolian sand were tested under lateral cyclic loading. The 4 replacement percentages of aeolian sand were 0%, 10%, 20%, and 30%. The seismic damage process of the specimens was studied by comparing the seismic indexes exhibited in the test. Then, the damage model of the specimens was studied. The results showed that the specimen whose replacement percentage of aeolian sand reached 30% had superior seismic damage performance. Its degree of damage was smaller than that of the other specimens under the same conditions. Its seismic indexes, including the bearing capacity, ductility, stiffness degradation, and energy dissipation capacity, performed much better than those of the other specimens. Besides, this paper proposes a damage model of an aeolian sand concrete column based on current results. This model can be used to evaluate the damage degree of this kind of column. Graphical Abstract: